(untitled) (Annals of Medical Research, 2023)
Aim: The most serious problem after curative treatment of non-metastatic lung cancer is disease recurrence. This study was designed to detect markers affecting disease recurrence and survival in operated lung cancer patients. Materials and Methods: In this study, the data of 109 patients diagnosed with lung cancer were analyzed retrospectively. Cut-off values for neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), alkaline phosphatase (ALP), and gamma glutamyl transpeptidase (GGT) were determined by performing ROC Curve analysis. According to these cut-off values, the patients were divided into two groups. Based on the cut-off value of the markers, their effects on both overall survival (OS) and disease-free survival (DFS) were examined. Results: In this study, the median OS of the patients was 53.9 months, and the median DFS was 20.6 months. The patients were re-evaluated by targeting the cut-off value of 2.35 for NLR obtained by ROC analysis. Below this value, mOS and mDFS were calculated as 78.2 and 43.2 months, respectively. Above this value, it was determined as 35.6 and 20.6 months, respectively. A similar evaluation was made for the PLR. As a result of the ROC analysis, the cut-off value was determined as 124.7. Below this value, mOS and mDFS were calculated as 72.4 and 36.9 months, respectively. Above this value, it was determined as 41.7 and 21.8 months, respectively. Both results were statistically significant (p<0.05). Conclusion: This study showed that NLR and PLR predict statistical significance for OS and DFS.